The application of artificial intelligence in spine surgery - Zhou, Shuai; Zhou, Feifei; Sun, Yu; Chen, Xin; Diao, Yinze; Zhao, Yanbin; Huang, Haoge; Fan, Xiao; Zhang, Gangqiang; Li, Xinhang (Frontiers in Surgery, 2022)
Due to its obvious advantages in processing big data and image information, the combination of artificial intelligence and medical care may profoundly change medical practice and promote the gradual transition from traditional clinical care to precision medicine mode. In this artical, we reviewed the relevant literatures and found that artificial intelligence was widely used in spine surgery. The application scenarios included etiology, diagnosis, treatment, postoperative prognosis and decision support systems of spinal diseases. The shift to artificial intelligence model in medicine constantly improved the level of doctors' diagnosis and treatment and the development of orthopedics.